Enhancing Sustainable IoT Systems Through a Goal-Oriented Requirements Analysis Framework - José Alfonso Aguilar-Calderón; Carolina Tripp-Barba; Aníbal Zaldívar-Colado; Pedro Alfonso Aguilar-Calderón; Pablo Alfonso Aguilar-Calderón (Applied Sciences)
The rapid expansion of the Internet of Things (IoT) has introduced significant challenges in requirements engineering (RE) due to the complexity of heterogeneous devices and dynamic user needs. Traditional RE methodologies often result in inefficient resource utilization and poor system performance. This research presents the goal-oriented requirements analysis (GORA) methodology, which optimizes requirement specification, resource allocation, and sustainability in IoT development. GORA addresses both functional and non-functional requirements, such as energy efficiency and security, while minimizing computational overhead and reducing resource wastage. The methodology integrates goal-oriented requirements analysis language i* and model-driven development (MDD) through a three-stage transformation process involving the i* RA model, UML class diagrams, and Python source code generation. A case study demonstrates how GORA improves system reliability, performance, and sustainability. Furthermore, an empirical evaluation was conducted in a simulated IoT environment, measuring key metrics such as energy consumption, latency, and code-generation error rate. A comparative analysis with existing RE and MDD approaches is also presented to highlight GORA’s advantages in feature coverage, sustainability support, and automation level. This work underscores the need for structured IoT RE frameworks and positions GORA as a foundation for future research in sustainable IoT development.